Therapy resistance in prostate cancer: mechanism, signaling and reversal strategies - Neha Thakur; Pallavi Singh; Aditi Bagri; Saumya Srivastava; Vinay Dwivedi; Asha Singh; Sunil Kumar Jaiswal; Sunny Dholpuria (Open Exploration Publishing Inc., 2024)
Prostate cancer (PC) depicts a major health challenge all over the globe due to its complexities in the treatment and diverse clinical trajectories. Even in the advances in the modern treatment strategies, the spectrum of resistance to the therapies continues to be a significant challenge. This review comprehensively examines the underlying mechanisms of the therapy resistance occurred in PC, focusing on both the tumor microenvironment and the signaling pathways implicated in the resistance. Tumor microenvironment comprises of stromal and epithelial cells, which influences tumor growth, response to therapy and progression. Mechanisms such as microenvironmental epithelial-mesenchymal transition (EMT), anoikis suppression and stimulation of angiogenesis results in therapy resistance. Moreover, dysregulation of signaling pathways including androgen receptor (AR), mammalian target of rapamycin/phosphoinositide 3 kinase/AKT (mTOR/PI3K/AKT), DNA damage repair and Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathways drive therapy resistance by promoting tumor survival and proliferation. Understanding these molecular pathways is important for developing targeted therapeutic interventions which overcomes resistance. In conclusion, a complete grasp of mechanisms and pathways underlying medication resistance in PC is important for the development of individualized treatment plans and enhancements of clinical outcomes. By studying and understanding the complex mechanisms of signaling pathways and microenvironmental factors contributing to therapy resistance, this study focuses and aims to guide the development of innovative therapeutic approaches to effectively overcome the PC progression and improve the survival rate of patients.